The Rietveld Refinement in the EXPO Software: A Powerful Tool at the End of the Elaborate Crystal Structure Solution Pathway - Angela Altomare; Francesco Capitelli; Nicola Corriero; Corrado Cuocci; Aurelia Falcicchio; Anna Moliterni; Rosanna Rizzi (Crystals, 2018)
The Rietveld method is the most reliable and powerful tool for refining crystal structure when powder diffraction data are available. It requires that the structure model to be adjusted is as close as possible to the true structure. The Rietveld method usually represents the final step of the powder solution process, in particular when a new structure is going to be determined and published. EXPO is a software able to execute all the steps of the solution process in a mostly automatic way, by starting from the chemical formula and the experimental diffraction pattern, passing through computational methods for locating the structure model and optimizing it, and ending to the Rietveld refinement. In this contribution, we present the most recent solution strategies in EXPO, both in reciprocal and direct space, aiming at obtaining models suitable to be refined by the Rietveld method. Examples of Rietveld refinements are described, whose results are related to different solution procedures and types of compounds (organic and inorganic).